Proceedings Electronic Components and Technology, 2005. ECTC '05.
DOI: 10.1109/ectc.2005.1441334
|View full text |Cite
|
Sign up to set email alerts
|

Drop Impact Reliability Testing for Lead-Free and Leaded Soldered IC Packages

Abstract: Portable electronic products such as cellular phones, PDAs, and MP3 units are increasingly designed for accidental drop. Repeated drop events can lead to solder joint failure and malfunction of these products. Hence board-level reliability drop testing is a useful way to characterize the drop durability of the printed circuit board with different soldered assemblies. Lead-free (or Pb-free) solders are replacing lead-based solders. Surface mounted electronic packages are getting smaller and with higher density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Clear solder joint cracks at the board side were found in the last remaining unit. However, for the PBGA package with OSP finish case, PCB copper traces breakage and resin cracks were the contributing factor for failure [1]. Lall et al [9] also reported PCB resin cracks in the drop test of chip scale package.…”
Section: Board Level Drop Test and Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Clear solder joint cracks at the board side were found in the last remaining unit. However, for the PBGA package with OSP finish case, PCB copper traces breakage and resin cracks were the contributing factor for failure [1]. Lall et al [9] also reported PCB resin cracks in the drop test of chip scale package.…”
Section: Board Level Drop Test and Analysismentioning
confidence: 97%
“…The details for drop impact test and result analysis can be referred to earlier reports [1,2], and a summary is given in this section. The Lansmont test machine was used to provide the drop impact load for board-level specimen with horizontal drop orientation and facedown packages as shown in Fig.…”
Section: Board Level Drop Test and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There are three main failure detection methods used in drop test reliability: post-drop (static) resistance measurement [12,15], event detection [16], and in-situ highspeed data acquisition [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a sense, all of these criteria are subjective, because, at this time, no scientific research has been done on the interconnection failure criteria. Determination of appropriate failure criteria is extremely important in order to observe first failures and when failures advance to different failure stages [17]. This variety of failure detection systems and failure criteria used by different researchers make the comparison of results difficult.…”
Section: Introductionmentioning
confidence: 99%